GIUSEPPE VERDI IN VICTORIAN LONDON - Massimo ZICARI (Studia Universitatis Babeş-Bolyai. Musica)
Despite the vast research on Verdi’s compositional as well as dramatic achievements, little attention seems to have been paid to the early reception of his works in Victorian London. A review of such periodicals as The Times, The Musical Times, The Athenaeum has drawn attention to two particular aspects of relevance; Verdi’s first operas impinged upon the model represented by Rossini’s light-spirited melodiousness and provoked a sense of general bewilderment; even when opera-goers began to show clear signs of appreciation and to crowd the theatres where Verdi’s operas were performed, critics continued to object to their value and to ascribe their success to the singers’ new vocal and dramatic skills.